Mechanism of Selective Inhibition of Yohimbine and Its Derivatives in Adrenoceptor α2 Subtypes. (28th April 2013) - Hai-Bo, Liu; Yong, Peng; Lu-qi, Huang; Jun, Xu; Pei-Gen, Xiao
Abstract : Some natural alkaloids from medicinal plants, such as yohimbine and its derivatives, have been reported with adrenoceptor (AR) α 2 subtypes inhibiting activity. In trying to address the possible mechanism of the action, a set of homology models of AR α 2 was built based on MOE. After that, docking and molecular dynamics methods were used to investigate the binding modes of yohimbine and its 2 derivatives in the active pocket of adrenoceptor α 2 subtype A, B, and C. The key interactions between the 3 ligands and the 3 receptors were mapped. Binding mode analysis presents a strong identity in the key residues in each subtype. Only a few differences play the key role in modulating selectivity of yohimbine and its derivatives. These results can guide the design of new selective AR α 2 inhibitors.